Cornel Iridoid Glycoside Inhibits Tau Hyperphosphorylation via Regulating Cross-Talk Between GSK-3β and PP2A Signaling - Yang, Cuicui; Li, Xuelian; Gao, Wenbin; Wang, Qi; Zhang, Li; Li, Yali; Li, Lin; Zhang, Lan (Frontiers in Pharmacology, 2018)
Neurofibrillary pathology contributes to neuronal dysfunction and correlates with the clinical progression of Alzheimer’s disease (AD). Tau phosphorylation is mainly regulated by a balance of glycogen synthase kinase-3β (GSK-3β) and protein phosphatase 2A (PP2A) activities. Cornel iridoid glycoside (CIG) is a main component extracted from Cornus ofﬁcinalis. The purpose of this study was to investigate the effects of CIG on GSK-3β and PP2A, thus to explore the mechanisms of CIG to inhibit tau hyperphosphorylation. The rat model of tau hyperphosphorylation was established by intraventricular injection of wortmannin and GF-109203X (GFX) to activate GSK-3β. The results showed that intragastrical administration of CIG inhibited tau hyperphosphorylation in the brain of rats induced by wortmannin/GFX. The results in vivo and in vitro exhibited that CIG inhibited tau hyperphosphorylation and GSK-3β over-activation. In the mechanism of action, CIG’s attenuating GSK-3β activity was found to be dependent on PI3K/AKT signaling pathway. PP2A catalytic C subunit (PP2Ac) siRNA abrogated the effect of CIG on PI3K/AKT/GSK-3β. Additionally and crucially, we also found that CIG inhibited the demethylation of PP2Ac at Leu309 in vivo and in vitro. It enhanced PP2A activity, decreased tau hyperphosphorylation, and protected cell morphology in okadaic acid (OA)-induced cell model in vitro. PP2Ac siRNA abated the inhibitory effect of CIG on tau hyperphosphorylation. Moreover, CIG inhibited protein phosphatase methylesterase-1 (PME-1) and demethylation of PP2Ac, enhanced PP2A activity, and decreased tau hyperphosphorylation in PME-1-transfectd cells. Taken together, CIG inhibited GSK-3β activity via promoting P13K/AKT and PP2A signaling pathways. In addition, CIG also elevated PP2A activity via inhibiting PME-1-induced PP2Ac demethylation to inhibit GSK-3β activity, thus regulated the cross-talk between GSK-3β and PP2A signaling and consequently inhibited tau hyperphosphorylation. These results suggest that CIG may be a promising agent for AD therapy.